A new species in the Simulium vernum group from the Alps of southern Germany: Simulium arminii (Diptera: Simuliidae) - Seitz, Gunther; Adler, Peter H. (Zootaxa, 2017)
Simulium arminii new species is described from the Alps of southern Germany. It is characterized by a broad trapezoidal ventral plate in the male, long slender arms of the genital fork in the female, a weakly developed or absent anterodorsal projection on the thinly woven cocoon, and a long median hypostomal tooth in the larva. The species is chromosomally similar to Simulium beltukovae (Rubtsov) but differs most conspicuously by the absence of a chromocenter. It is known from two small, springfed streams above the timber line, in association with Prosimulium latimucro (Enderlein) and Simulium bavaricum Seitz and Adler.